Floating offshore wind turbine aerodynamics: Trends and future challenges. (December 2021) - Micallef, Daniel; Rezaeiha, Abdolrahim
Abstract: Offshore wind turbines present novel challenges to the field of rotor aerodynamics because of complex behaviours associated with six degrees of freedom motions of the platform. The number of scientific articles on these specific issues has been steadily increasing during the past ten years, reflecting the criticality of aerodynamics to overcome the specific barriers in this area. In this work, we aim to comprehensively review the present literature in order to identify the existing knowledge gaps in this field of research and provide an outlook for future directions. This paper is not purely about aerodynamics as an isolated element of floating offshore wind turbine science. Rather, due to the multi-physics nature of the system, we emphasise the current trends in aerodynamics in relation to other fields such as platform hydrodynamics and control. Critical analysis of the literature reveals that the most common approaches are to study the problem in a coupled or uncoupled manner. The latter is generally done by prescribing platform motions. The existing literature has been so far mainly focused on an isolated solo floating turbine and the studies on the interactions between the floating turbines are scarce. These trends are critically assessed in order to provide the reader with a holistic overview of the current direction. We also present six major challenges in order to provide a future perspective of the existing research opportunities in floating offshore wind turbine aerodynamics. Highlights: Floating offshore wind turbine aerodynamics research gaps identified. Challenges to be addressed concurrently with neighbouring fields. Trends towards multi-physics approaches identified. Floating offshore wind farm wakes need more investigations. Localised flow phenomena due to 6DOF platform motions should be studied.